Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah pada Mata Pelajaran Matematika Kelas V SDN 51 Sungai Raya - Masika Rosadi Anna; Dessy Setyowati; Suriayana Suriayana (Indo-MathEdu Intellectuals Journal, 2026)
The low mathematical problem-solving ability of elementary school students, especially in fractions, remains a common problem in learning. This condition is influenced by the dominance of conventional learning that does not actively involve students in the thinking and problem-solving process. Therefore, a learning model is needed that can encourage student involvement and develop higher-order thinking skills. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the mathematical problem-solving ability of fifth-grade students at SDN 51 Sungai Raya. The study used a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The research sample consisted of two classes: the experimental class that implemented the PBL model and the control class that used conventional learning. The research instrument was an essay test compiled based on Polya's problem-solving indicators. Data analysis techniques included a normality test, a homogeneity test, and a t-test to examine the difference in the average post-test results. The analysis results showed a significance value of 0.000 (<0.05), which means there was a significant difference between the two groups. The average problem-solving ability of students in the experimental class was higher than that of the control class. Thus, the PBL model has a positive effect on students' mathematical problem-solving ability.